2011
DOI: 10.1111/j.1741-2358.2011.00545.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status, dietary intake and oral quality of life in elderly complete denture wearers

Abstract: Nutritional status, dietary intake and oral quality of life in elderly complete denture wearers Background and objective: The prevalence of malnutrition increases with age because of many factors. Edentulousness leads to the avoidance of many types of foods. The aim of this study was to determine whether elderly complete denture wearers have a higher risk of malnutrition than dentate controls. Material and methods: A Mini-Nutritional Assessment (MNA) and a 3-day dietary record were compiled for a group of full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
73
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 44 publications
3
73
1
8
Order By: Relevance
“…These results are similar to those of Cousson in France, who reported that the control group with no chewing difficulty had a greater fat intake than that in their chewing difficulty group [34]. In contrast, Hung et al [35] suggested that edentulous US women had a significantly high intake of saturated fat, trans-fat, and cholesterol.…”
Section: Discussionsupporting
confidence: 86%
“…These results are similar to those of Cousson in France, who reported that the control group with no chewing difficulty had a greater fat intake than that in their chewing difficulty group [34]. In contrast, Hung et al [35] suggested that edentulous US women had a significantly high intake of saturated fat, trans-fat, and cholesterol.…”
Section: Discussionsupporting
confidence: 86%
“…After taking into account all these considerations, the GOHAI was used for this study. The methodology used in the present study is similar to that of previous studies [26-28], though it presents some biases and weaknesses. First, the lack of investigator calibration could be a limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it could be expected that patients with multiple untreated carious lesions would be at higher risk of developing metabolic diseases and diabetes than persons with healthy teeth. Many reports suggest that an impaired masticatory function favours inappropriate diet [N'gom and Woda, 2002] and poor oral health status is associated with the selection of soft food, easy to chew and with avoidance of foods rich in dietary fibre and nutrients [Johansson et al, 1994;Sheiham et al, 2002;Nowjack-Raymer and Sheiham, 2003;de Oliveira and Frigerio, 2004;Cousson et al, 2012]. Such diets increase the risks for cardiovascular diseases.…”
Section: Effects Of Carious Process On Nutritionmentioning
confidence: 99%